Ten Years of Diphtheria Toxin Testing and Toxigenic Cutaneous Diphtheria Investigations in Alberta, Canada: A Highly Vaccinated Population. (20th August 2021) - Marshall, Natalie C; Baxi, Maulik; MacDonald, Clayton; Jacobs, Angela; Sikora, Christopher A; Tyrrell, Gregory J
Abstract: Background: Respiratory diphtheria is a potentially fatal toxin-mediated disease that is rare among highly vaccinated populations. Cutaneous infections with toxigenic Corynebacterium diphtheriae are most commonly linked to travel to an endemic region. Corynebacterium ulcerans has emerged as a predominant, locally acquired cause of respiratory and cutaneous diphtheria in Western Europe. Recently, public health agencies from several highly vaccinated regions expanded their guidelines to investigate toxigenic cutaneous diphtheria regardless of travel history. With relatively unknown epidemiology of C diphtheriae in North America, and increasing diphtheria toxin testing over the last decade, this change could lead to substantial increases in public health investigations with unclear benefits. Methods: This study examined the diagnostic and public health benefits of toxigenic cutaneous diphtheria investigations in the highly vaccinated population of Alberta, Canada, where travel history is not required for cutaneous diphtheria investigations. All C diphtheriae isolates collected between 2010 and 2019 were reviewed for specimen source, toxigenicity, biovar, and associated clinical and public health data. Results: Of these, 5% of C diphtheriae isolates were toxigenic and 82% were isolated from cutaneous sites. Three cases of toxigenic cutaneous disease were identified, none from patients with recent travel. Contact tracing identified asymptomatic C diphtheriae colonization among 0%–26% of close contacts, with identical isolate profiles among colonized contacts and primary cases. Conclusions: Cutaneous diphtheria in nonendemic regions warrants public health investigation regardless of travel history and overall vaccination levels. This study underscores the importance of including C ulcerans in public health guidelines to assess the overall prevalence and epidemiology of toxigenic corynebacteria.